Ripensare le politiche di salute nell’era neoliberista. Welfare mix e sofferenza psichica. Quali spazi d’intervento per la società civile? - Cammarota, Antonella; Raffa, Valentina (SocietàMutamentoPolitica, 2021)
The coronavirus pandemic that has brought Italy (like many other countries) to its knees brings to the surface in a brutal way the criticality of the health policy choices taken by the government in the last thirty years, guided by the principle of subordination of the quality of care to cost efficiency. The priority has been to maximize profit by sacrificing the quality of care and health services. All this forces us to redefine the terms and categories with which we read and interpret today the issues related to the physical and mental health of citizens and the policies that govern it. Starting from this, the aim of this article is to reflect on the limits of contemporary health policies and the urgency of rethinking them in terms of a greater capacity to reconcile people’s needs with a better use of public resources. To this end, the article will focus on bottom-up health policy practices that try to guarantee, at the same time, the quality of care and a better use of health spending, through the analysis of the experience of the Solaris association in Rome working in the field of mental health.